Androgen Receptor Promotes Tamoxifen Agonist Activity by Activation of EGFR in ERα-Positive Breast Cancer - Ciupek, Andrew (Breast Cancer Res Treat, 2015)
PURPOSE: Tamoxifen (Tam) resistance represents a significant clinical problem in estrogen receptor (ER) -positive breast cancer. We previously showed that decreased expression of Rho guanine nucleotide dissociation inhibitor (Rho GDI), a negative regulator of the Rho GTPase pathway, is associated with Tam resistance. We now discover that androgen receptor (AR) is overexpressed in cells with decreased Rho GDI and seek to determine AR’s contribution to resistance. METHODS: We engineered ER -positive cell lines with stable knock-down (KD) of Rho GDI (KD cells). Resistance mechanisms were examined using microarray profiling, protein-interaction studies, growth and reporter gene assays, and Western blot analysis combined with a specific AR antagonist and other signaling inhibitors. RESULTS: Tam-resistant tumors and cell lines with low Rho GDI levels exhibited upregulated AR expression. Microarray of Rho GDI KD cells indicated that activation of EGFR and ER was associated with Tam treatment. When AR levels were elevated interaction between AR and EGFR was detected. Constitutive and Tam-induced phosphorylation of EGFR and ERK1/2 was blocked by the AR antagonist Enzalutamide, suggesting that AR-mediated EGFR activation was a mechanism of resistance in these cells. Constitutive ERα phosphorylation and transcriptional activity was inhibited by Enzalutamide and the EGFR inhibitor gefitinib, demonstrating that AR-mediated EGFR signaling activated ER. Tam exhibited agonist activity in AR over-expressing cells, stimulating ERα transcriptional activity and proliferation, which was blocked by Enzalutamide and gefitinib. CONCLUSIONS: We describe a novel model of AR-mediated Tam resistance through activation of EGFR signaling leading to ER activation in ER -positive cells with low expression of Rho GDI.